Making the Bible safe for democracy: american Methodists and the First World War - Wesley, Cindy K. (Journal of the bible and its reception, 2017)
The article examines the depiction of the First World War in literature published by the Methodist Episcopal Church for Sunday Schools, mission societies, young people’s organizations and a general church readership. Methodist Episcopal Church authors highlighted the biblical themes of righteousness, Christ-like self-sacrifice, and the Kingdom of God as they justified American involvement in the Great War.